The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/frsus.2022.809700
|View full text |Cite
|
Sign up to set email alerts
|

Re-organise: Game-Based Learning of Circular Business Model Innovation

Abstract: This study furthers game-based learning for circular business model innovation (CBMI), the complex, dynamic process of designing business models according to the circular economy principles. The study explores how game-play in an educational setting affects learning progress on the level of business model elements and from the perspective of six learning categories. We experimented with two student groups using our game education package Re-Organise. All students first studied a reader and a game role descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In Greece, research showed the positive effect of learning on the integration of multimodal educational materials in science, technology, engineering, and mathematics (STEM) in early childhood and the adaptive gamification in the teaching of science at the preschool and elementary education levels (Zourmpakis et al, 2020;Tsoukala, 2021). Similarly, gameplay experience enhanced students' learning ability for circular business (Lange et al, 2022). The serious game In the Loop facilitated the educational process for engineering students to adopt CE strategies (Whalen et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Greece, research showed the positive effect of learning on the integration of multimodal educational materials in science, technology, engineering, and mathematics (STEM) in early childhood and the adaptive gamification in the teaching of science at the preschool and elementary education levels (Zourmpakis et al, 2020;Tsoukala, 2021). Similarly, gameplay experience enhanced students' learning ability for circular business (Lange et al, 2022). The serious game In the Loop facilitated the educational process for engineering students to adopt CE strategies (Whalen et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Netherlands Re-organise: Game-Based Learning of Circular Business Model Innovation [26]. Industrial Symbiosis: towards a design process for eco-industrial clusters by integrating Circular Economy and Industrial Ecology perspectives [5].…”
Section: Koreevarmentioning
confidence: 99%
“…Aid G. [22,23] from Sweden, Angelis-Dimakis A. [24,25] from Greece and the United Kingdom, and Koreevar [5,26] from the Netherlands are in second place among the authors with the highest number of publications on the subject. Aid G. [22] developed a tool to strategically facilitate the implementation of industrial symbiosis, identifying the best possibilities for creating networks, exchanging flows, and informational needs, as well as the main obstacles and opportunities for a successful transition while exploring new business models [23].…”
Section: Main Topics Of Research Authors and Journalsmentioning
confidence: 99%